La résilience face à la normativité et la solidarité des territoires - Julie Daluzeau; Mathilde Gralepois; Clément Oger (EchoGéo)
The maintenance and development of urban centers in floodplain question the effectiveness of prevention policies based on urbanization’s control. This paper critically assesses urban resilience in risk managers’ speech during the revision of the Plan Risk Prevention Val Tours - Val de Luynes. This concept reveals the limits of the regulatory flood from a common standard. Also, adaptability and self-organization of the people is a necessary condition to ensure the survival of a society when a disturbance appears. Far from encouraging practices of cooperation and solidarity, paradigm shifts and scale-induced resilience have to face a lack of trust between the government and the population.